Biomechanical Finite Element Method Model of the Proximal Carpal Row and Experimental Validation - Marqués, Rafael; Melchor, Juan; Sánchez-Montesinos, Indalecio; Roda, Olga; Rus, Guillermo; Hernández-Cortés, Pedro (Frontiers in Physiology, 2022)
The Finite Element Method (FEM) models are useful tools in order to create an idea of the behaviour of any structure/complex. The complexity of the joints , materials, attachment areas and boundary condition is an open issue in biomechanics that needs to be addressed. Particularly, the scapholunate instability is a main cause of wrist pain and disability among patients of all ages. It is needed of a better understanding of the pathomechanics to develop new effective treatments. Previous models have emulated joints like the ankle or the knee but there are not many about the wrist joint. The elaboration of realistic computational models of the carpus can give critical information to biomedical researchers and surgeon for the development new surgical reconstructions. Hence, a 3D model of the proximal carpal row has been created through DICOM images, making a reduced model of the wrist. The materials, contacts and ligaments definition were made via an open source software in order to extract results to make a references comparison. In this way, the results are consistent with the hypothesis, considering the limitations of the model though. Also, an experimental testing is performed, successfully validating the linear strengh values of the scapholunate ligament from the literature.